2020
DOI: 10.4162/nrp.2020.14.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and modifiable factors contributing to hyper-LDL-cholesterolemia prevalence in nationwide time series data and the implications for primary prevention strategies

Abstract: BACKGROUND/OBJECTIVES: A number of studies examined secular trends in blood lipid profiles using time series data of national surveys whereas few studies investigated individual-level factors contributing to such trends. The present study aimed to examine secular trends in dietary and modifiable factors and hyper-LDL-cholesterolemia (HC) prevalence and evaluate their associations using time series data of nationwide surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Pooled analyses also showed that milk and dairy product intake was associated with 18% decreased risks for both elevated triglycerides and low HDL cholesterol, with a pooled estimate (95% CI) of 0.82 (0.76-0.89) for both outcomes (11). In contrast, we did not find any associations between the prudent dietary pattern and dyslipidemia and its components, despite the high content of saturated fatty acids in dairy products (36,37).…”
Section: Discussioncontrasting
confidence: 47%
“…Pooled analyses also showed that milk and dairy product intake was associated with 18% decreased risks for both elevated triglycerides and low HDL cholesterol, with a pooled estimate (95% CI) of 0.82 (0.76-0.89) for both outcomes (11). In contrast, we did not find any associations between the prudent dietary pattern and dyslipidemia and its components, despite the high content of saturated fatty acids in dairy products (36,37).…”
Section: Discussioncontrasting
confidence: 47%
“…In addition, hyperhomocysteinemia (HHcy) is usually a consequence of a reduction in the activity of enzymes involved in homocysteine (Hcy) metabolism, which is generally a crucial and modifiable risk factor for CVD ( 6 ). Rapid economic growth, coupled with the increasing adoption of unhealthy lifestyles, has caused a continuous increase in the incidence of cardiovascular risk factors, which in turn has led to a substantial increase in the CVD burden in China ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…And it is being raised year by year as a risk factor for death (Pirillo et al, 2021). It is noteworthy that with rapid economic development, the faster rate of urbanization, high cholesterol and high-calorie diet intake, and unhealthy lifestyle are considered to be the main causes of the development of hyperlipidemia (Baik, 2020;Taddei et al, 2020). There is an urgent need to develop appropriate medications for successful treatment and prevention.…”
Section: Introductionmentioning
confidence: 99%